2012
DOI: 10.1021/pr3002639
|View full text |Cite
|
Sign up to set email alerts
|

Return of the Metabolic Trajectory to the Original Area after Human Bone Marrow Mesenchymal Stem Cell Transplantation for the Treatment of Fulminant Hepatic Failure

Abstract: Our recent study first demonstrated that human bone marrow mesenchymal stem cell (hBMSC) transplantation could prevent death from fulminant hepatic failure (FHF) in pigs. To further clarify the metabolic mechanism of hBMSC transplantation in FHF, the plasma collected from FHF pigs that received transplantation of hBMSCs was examined using metabolic analysis to identify the key molecular markers that regulate recovery. The results showed that obvious metabolic disturbance occurred during FHF, whereas the hBMSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It has also been suggested that depletions of lysoPCs could occur through reduced phospholipase A2 activity affecting hydrolysis of PCs to lysoPCs [2] or reduced activity of lecithin:cholesterol acyltransferase (LCAT) which affects lysoPC production by transacylation of the sn-2 fatty acid residue of lecithin to free cholesterol [11] . In a recent study [31] of d -galactosamine induced fulminant hepatic failure, long chain PCs and lysoPCs were depleted and then were restored through stem cell transplantation. Thus, collectively, the data suggest that both PCs and lysoPCs play a significant functional role in global liver injury and/or the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that depletions of lysoPCs could occur through reduced phospholipase A2 activity affecting hydrolysis of PCs to lysoPCs [2] or reduced activity of lecithin:cholesterol acyltransferase (LCAT) which affects lysoPC production by transacylation of the sn-2 fatty acid residue of lecithin to free cholesterol [11] . In a recent study [31] of d -galactosamine induced fulminant hepatic failure, long chain PCs and lysoPCs were depleted and then were restored through stem cell transplantation. Thus, collectively, the data suggest that both PCs and lysoPCs play a significant functional role in global liver injury and/or the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the metabolic balance is an important regulator of MSC‐based regenerative medicine. In addition to inhibiting hepatocyte apoptosis, MSCs participated in maintaining metabolic balance by regulating amino acids, bile acids, sphingolipids, acylcarnitines and glycerophospholipids in liver cells to attenuate liver injury in ALF rats . Liver transplantation always has a high rejection rate, and although liver tissue is a tolerogenic organ with adaptive systems, acute graft‐vs‐host disease is a serious and life‐threatening complication of LT .…”
Section: The Potential Mechanisms By Which Msc Administration Can Trementioning
confidence: 99%
“…In addition to inhibiting hepatocyte apoptosis, MSCs participated in maintaining metabolic balance by regulating amino acids, bile acids, sphingolipids, acylcarnitines and glycerophospholipids in liver cells to attenuate liver injury in ALF rats. 26 Liver transplantation always has a high rejection rate, and although liver tissue is a tolerogenic organ with adaptive systems, acute graft-vs-host disease is a serious and life-threatening complication of LT. 27 More recently, MSC transplantation has been recognized as a novel treatment for preventing graft rejection and treating autoimmune diseases such as graft-vs-host disease via immunomodulatory effects mediated by cell-to-cell interactions and secreted cytokines. 28 MSCs improved the prognosis of LT animals by suppressing hepatocyte apoptosis, KC apoptosis, Th1/Th17 infiltration, chemokine release and inflammatory cell infiltration.…”
Section: The P Otential Mechanis Ms By Whi Ch Msc Adminis Tr Ati Onmentioning
confidence: 99%
“…Cai et al established that BM-MSC transplantation decreased ALT and AST levels, downregulated Bax protein, and increased Bcl-2 expression compared with an acute liver injury (ALI) model [ 49 ]. In addition, MSC transplantation in rats can regulate liver and blood metabolic disorders, such as the imbalance of amino acids, bile acids, sphingolipids, acylcarnitines, and glycerophospholipids, which would increase proliferation and decrease apoptosis in hepatocytes [ 48 , 52 ]. Salomone et al showed that AT-MSC transplantation in rats with ALI decreased AST, ALT, and prothrombin time (PT) and reduced liver isoprostanes, 8-hydroxyguanosine, and nitrite-nitrate levels but maintained glutathione levels.…”
Section: Introductionmentioning
confidence: 99%